Ultrasonic studies on hydration of carboxylic acids, amino acids and peptides in aqueous ethanolic solutions - JUSZKIEWICZ, Adam (Archives of Acoustics, 1985)
Hydration numbers of the simplest carboxylic acids, amino acids and di- and tripeptides were determined by measurements of ultrasonic velocity in the ethanolic-aqueous solutions. Hydration numbers of the functional groups pre-sent in the amino acids and peptides were also determined.